THE EFFECTIVENESS OF START TRIAGE AS AN ALTERNATIVE TO ESI IN MANAGING MASS CASUALTY INCIDENTS (MCI) IN THE EMERGENCY DEPARTMENT: A SYSTEMATIC LITERATURE REVIEW : MANAGING MASS CASUALTY INCIDENTS - Al-Mohades ades; Nadya Puteri; Zaqyyah Huzaifah (STIKes Mandala Waluya Kendari, 2026)
Background: The Emergency Department (ED) frequently faces patient overcrowding during Mass Casualty Incidents (MCI). The Emergency Severity Index (ESI) is often considered too complex and time-consuming during patient surges. The Simple Triage and Rapid Treatment (START) method has been proposed as an alternative due to its rapid application. This study aims to evaluate the effectiveness of START compared to ESI in terms of speed, accuracy, and ease of use in disaster situations. Methods: This study employed a Systematic Literature Review design based on the PRISMA 2020 guidelines. Searches were conducted in electronic databases for articles published between 2015 and 2025. Of 50 identified articles, 25 met the inclusion criteria and were analyzed. Results: The findings indicate that START is significantly faster (less than 60 seconds per patient) than ESI (3–5 minutes) effectively reducing patient flow bottlenecks. While ESI shows high specificity for non-trauma cases, START demonstrates up to 100% sensitivity in identifying critically injured trauma patients. START also imposes a lower cognitive burden on nurses in high-stress conditions. Conclusion: These findings support START as an effective alternative triage system during disaster response to manage trauma patient surges.